Linking The Effect Of Supervisor Leadership Styles On Job Performance Among Retail Sectors In Kuching, Sarawak : Job Satisfaction As Mediator - Nurul Ain Syafiqah, Mohd Sabri (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study is focus at finding the relationship between the effectiveness leadership styles (transformational and transactional leadership styles) and job performance through job satisfaction as mediator. Quantitative method had been used in this study where the data were collected by using questionnaires (Google form) as the instrument. The data was collected from 160 samples in three of retail sectors companies in Kuching, Sarawak. The data were then analyzed by using both descriptive and inferential statistics. Hence, Spearman’s Correlation, Independent Sample T-Test and One-Way Anova test procedure was used to measure the relationships between the independent variables and dependent variables and also for the demographic characteristics. The findings have shown that there is a significant relationship for the five first hypothesis of each variables. It was also found that the transformational leadership styles implemented is the most dominant factor affecting the job performance. The researcher has recommended a focus on the study that may help the organizations and future researches for the future needs.